TOPOGRAPHY AND GEOID EFFECTS OF TIME-DEPENDENT CONVECTION - Ritzert M. (My University, 1995)
Time series of the boundary deformations and the geoid signal of non-steady convection with pressure- and temperature-dependent viscosity are analysed to obtain information on the uncertainty of estimates of the vertical viscosity structure due to time dependence. The amplitudes of the boundary deformations and the geoid are typically lower than at steady state. Thus they are closer to the values observed on earth. During short episodes, however, strongly increased amplitudes are observed which are caused by rising plumes approaching the upper thermal boundary layer or by boundary layer instabilities which are advected into the main downflow. The temporal variability of the geoid strongly exceeds the geoid effects from neglecting lateral viscosity variations. Furthermore, the vertical viscosity profile itself has been found to be strongly time dependent. These factors may be severe sources of uncertainty when the viscosity depth structure of the mantle is inferred from the geoid without taking the time dependence into account.